Peran Karakteristik Individu sebagai Moderatoe Pengaruh Kepuasan, Kepercayaan dan Komitmen terhadap Loyalitas (studi pada nasabah bank syariah di Kabupaten Kudus) - Arwani, Mokhamad; Taufik, -; Masluri, - (Jurnal Sosial Budaya, 2011)
The low growth of Islamic bank customers is because of the weak of Islamic bank customers. One of the important evidences of customerâs loyalty is satisfaction. When customers are satisfied, they will not Â hesitate to invite others to be the customers of the Islamic banks.The main focus of this research is to reveal and interpret the mediation role of the relationship marketing (trustÂ  andÂ  commitment) between satisfaction and loyalty,Â  asÂ  wellÂ  asÂ  to testÂ  theÂ  moderator role ofÂ  individual characteristics in relation with the influence of satisfaction on loyalty. The analysis showed that customers who are satisfied will be loyal to Islamic banks if the customer have adequate educational background and knowledge about Islamic banking. The satisfied customers will enhance long-term relationship with the Islamic banks in form of mutual trust, good communication, and trust that the bank will provide good services. The satisfied customers will enhance the mutual trust and good communication, which eventually create customers loyalty.